The Sociological Perspective on The Study of The Living Law: Is It a Part of Legal Discipline or Social Discipline? - Lestarini, Ratih (Magister of Law, Faculty of Law, University of Mataram, 2023)
The legalistic positivist Civil Law tradition still dominates legal thinking in Indonesia. Therefore, law is often only defined as legislation. Law that is realized in norms is postulated in the form of laws. Whereas outside state law there is also a law that grows and develops in society which has a very effective force. The law is known in the concept of The Living Law which is translated by academics in Indonesia as Customary Law, where the law is realized in the attitude of legal action. Its existence as an embodiment of the original Indonesian Legal system is different from the Civil Law legal system. The problem is when each claims the truth of the law. Meanwhile, if we look at the legislation, the existence of Customary Law as The Living Law is highly dependent on state recognition. Therefore, to understand and explain it brings methodological consequences that use an external perspective. The question that arises is whether the law embodied in the attitude of legal action can be interpreted sociologically? If it can, is this sociological study part of the study in the discipline of law or is it a study of social disciplines? This paper will argue about the importance of an interdisciplinary perspective in the study of legal disciplines, such as the Sociology of Law in the study of The Living Law.